Tingkat Kepatuhan Masyarakat terhadap Pembayaran PBB : Perspektif Sosial dan Budaya - Ananda Febriyani; Sheila Afriliani; Vicky Febima Andrerico; Ahmad Ghani Bilhaq Pasaribu (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to describe and analyze the level of community compliance in paying Land and Building Tax (PBB) from a social and cultural perspective. A qualitative approach was used with a case study method in one of the villages in region X which has varying levels of compliance. Data were collected through in-depth interviews, participatory observation, and documentation, with key informants consisting of taxpayers, community leaders, and village officials. The results of the study indicate that community compliance with PBB payments is not solely influenced by economic and regulatory factors, but also by social values ​​such as mutual cooperation, trust in local government, and cultural norms that live in the community. In addition, perceptions of tax fairness and the real benefits of paying taxes also influence community attitudes. These findings indicate the importance of a cultural approach in tax compliance improvement strategies, especially in areas with strong social characteristics. This study recommends the need for contextual and collaborative PBB socialization with local leaders to build tax awareness based on local values.